On the Interrelation of the Concepts of Corruption, Corruption-Related Crimes and Bribery in the Legislation of the Republic of Kazakhstan and the Russian Federation - E. I. Chekmezova; Z. D. Ermеkova (Сибирское юридическое обозрение)
Corruption has become a transnational phenomenon that threatens the stability and security of the society. Moreover, this phenomenon has a negative impact on various spheres of society, which undermines the democratic institutions and values of any state. Statistical data from Russia and Kazakhstan indicate that the number of corruption-related crimes has been increasing, thus pointing at the lack of effective measure of combating this phenomenon. In the studies and normative acts of Russia and Kazakhstan regulating the issues of combating corruption, the concept of corruption is given a different interpretation. In this regard, using the analogy with the legislation of Kazakhstan, the authors propos a new understanding of corruption, which should be codified in the relevant Federal Law of Russia. In addition, in order to improve the quality of legal regulation of anti-corruption in the General part of the Criminal Code of the Russian Federation, it is necessary to consolidate the list of corruption-related crimes. There are quite a lot of definitions of the term bribery in academic literature. At the same time, most authors believe that it should be considered through criminal and legal components. Bribery is one of the most important elements of corruption, responsibility for it is provided in articles 366, 367, 368 of the Criminal Code of the Republic of Kazakhstan and articles 290, 291, 2911, 2912 of the Criminal Code of the Russian Federation. In the Criminal Code of the Republic of Kazakhstan, the offer and promise of a bribe (including the offer and promise of mediation in bribery) is not criminalized. In this connection, the authors, with regards to the requirements of the UN Convention against Corruption on criminalization of acts of promising, offering mediation in bribery, and relying on the practices of the legislator of the Russian Federation, propose to amend Article 368 of the Criminal Code of the Republic of Kazakhstan (Mediation in Bribery). The authors believe that the discussed changes and additions will result in a legal framework for combating corruption and defining its boundaries.